En route to a PhD: Mapping the journey through a sensemaking lens - Coetzee, M.; Wilkinson, A. (South African Journal of Higher Education, 2020)
Doing a PhD is for most scholars a demanding and emotionally strenuous experience, frequently resulting in potentially promising researchers succumbing to despair soon after embarking on the journey. However, those who complete their doctoral studies recollect subsequently both the frustrations and exciting experiences encountered. This article describes one researcher’s ruminations to make sense of the extensive systematic analysis utilised in a quest to obtain a PhD and to understand the academic essence of the scholarly contribution of her PhD. Using the seven fundamental properties of Weick’s (1995) sensemaking theory as the theoretical lens, the researcher reflects on the experiences and observations faced en route to completing her PhD. The seven properties form the backdrop of the researcher’s qualitative sensemaking methodology in which she formulated three key phases to illustrate her sensemaking road, namely Mapping the Journey, Travelling the Road, and Reaching the Destination. This article reinforces the extent of the challenges a PhD study holds and provides detail of and insight into the application of the sensemaking theory that may be useful to postgraduate researchers and supervisors involved in qualitative inquiry.